2018
DOI: 10.1292/jvms.17-0403
|View full text |Cite
|
Sign up to set email alerts
|

An efficient method for saliva collection from mature pigs to determine their enzymatic and electrolytic profiles

Abstract: In this study, a novel ‘rope-assisted swab method’ for the collection of saliva samples from 45 adult pigs was established and validated. This method was efficient for harvesting 2 milliliters or more of saliva from each of the pigs for subsequent analyses within two min. The amount of α-amylase and lipase in the collected saliva samples was between 38−6,655 and 2−52 U/l, respectively. For HCO3− and electrolytes, the range was between 9−40, 15−76, 4.3−48.5 and 7−65 mM for HCO3−, Na+, K+ and Cl−, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Similar to ammonia, serum bicarbonate is considered a predictor of clinical outcomes in cases of sepsis, as low serum bicarbonate is associated with significantly increased in-hospital mortality [ 17 ]. The concentrations of bicarbonate obtained in our study are in the range of the values previously reported in the saliva of pigs, giving also similar values to those in humans [ 18 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to ammonia, serum bicarbonate is considered a predictor of clinical outcomes in cases of sepsis, as low serum bicarbonate is associated with significantly increased in-hospital mortality [ 17 ]. The concentrations of bicarbonate obtained in our study are in the range of the values previously reported in the saliva of pigs, giving also similar values to those in humans [ 18 ].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, serum bicarbonate is a good predictor of clinical outcomes in sepsis alone or combined with other markers [ 17 ]. Bicarbonate has been measured in the saliva of pigs, giving similar values to that in humans [ 18 ]. Recently, changes in concentrations of ammonia and bicarbonate were detected in horses with gastric ulcers [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Saliva was collected using the cable-lock-assisted swab method outlined in Akhtar et al [33]. Briefly, Salivette ® tubes with plain cotton swabs (Starstedt AG & Co.), specialized for collection and processing methods were used to ensure the hygienic sampling of saliva.…”
Section: Biofluid Collectionmentioning
confidence: 99%
“…The electrolyte concentrations of swine saliva were first studied in 1966 [154], analysing sodium, potassium, calcium, and phosphate. Later, chloride and bicarbonate were also determined in porcine saliva [155]. The latter can neutralise acid and acts as a buffer.…”
Section: I62 Contentmentioning
confidence: 99%